(untitled) (Teaching and Learning Inquiry, 2013)
Much of the literature in the field of the Scholarship of Teaching and Learning (SoTL) discusses the need for SoTL and how critical inquiry can support teaching and learning. This article supports much that has been said before but further suggests that, in order for SoTL to fulfil its ambitions, practitioner-researchers should consider the way that their environment shapes them. It is suggested that, by reflecting on their specific context, practitioner researchers can engage in a practice that is more suited to supporting those who learn within such a context. Further, it is recommended that sharing such reflections through published work could help secure the development of such practice within and across the academy.